Tomorrow never dies - Spottiswoode, Roger; Feirstein, Bruce; Wilson, Michael G.; Broccoli, Barbara (MGM/UA Home Video ; distributed in the Philippines by Viva Video, 2000)
Just as a media mogul unveils his new global news service, a British warship is attacked in Chinese territory. Agent James Bond teams with a beautiful Chinese spy to discover the truth before war breaks out.